Exploring the Potential of Nuciferine in Diabetes Management via PTGS2 Pathway Targeting by Network Analysis and in-silico Modeling Approach - Murthy, Sridevi Narayana; Margesan, Thirumal (Current Medicinal Chemistry, 2025)
<span class=
Keywords: network pharmacology